Randomised controlled trial evaluating effects of morphine on plasma adrenaline/noradrenaline concentrations in newborns. Issue 1 (21st December 2004) - Simons, S H P; van Dijk, M; van Lingen, R A; Roofthooft, D; Boomsma, F; van den Anker, J N; Tibboel, D
Abstract : Objectives: To determine the effects of continuous morphine infusion in ventilated newborns on plasma concentrations of adrenaline (epinephrine) and noradrenaline (norepinephrine) and their relation to clinical outcome. Design: Blinded, randomised, placebo controlled trial. Setting: Level III neonatal intensive care units in two centres. Patients: A total of 126 ventilated neonates (inclusion criteria: postnatal age <3 days, duration of ventilation <8 hours, indwelling arterial catheter for clinical purposes; exclusion criteria: severe asphyxia, severe intraventricular haemorrhage, major congenital anomalies, neuromuscular blockers). Interventions: Plasma adrenaline and noradrenaline concentrations were determined in patients during blinded morphine (n  =  60) and placebo (n  =  66) infusion (100 μg/kg plus 10 μg/kg/h). Results: Plasma concentrations at baseline (nmol/l with interquartile range in parentheses) were comparable in infants treated with morphine (adrenaline, 0.22 (0.31); noradrenaline, 2.52 (2.99)) or placebo (adrenaline, 0.29 (0.46); noradrenaline, 2.44 (3.14)). During infusion, median adrenaline concentrations were 0.12 (0.28) and 0.18 (0.35) and median noradrenaline concentrations were 2.8 (3.7) and 3.8 (4.0) for the morphine and placebo treated infants respectively. Multivariate analyses showed that noradrenaline (p  =  0.029), but not adrenaline (p  =  0.18), concentrations were significantly lower in the morphine group than the placebo group. Furthermore, noradrenaline concentrations were related to the length of stay in the neonatal intensive care unit. Conclusions: Continuous morphine infusion significantly decreased plasma noradrenaline concentrations in ventilated newborns compared with placebo treatment. The results of this study support the idea that routine morphine administration decreases stress responses in ventilated neonates.